1996
DOI: 10.1093/oxfordjournals.ndt.a027092
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus and skin hydration during dialysis

Abstract: Reduced stratum corneum hydration correlates with pruritus in patients on maintenance haemodialysis and peritoneal dialysis, and may be alleviated by simple emollient therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
133
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 12 publications
9
133
1
2
Order By: Relevance
“…Exacerbation of pruritus with dry skin was reported by 13 (65%) patients. Morton et al 8 revealed lower hydration of stratum corneum in uremic patients with pruritus and dry skin promotes sensation of itch by lowering the threshold for itch. In our study majority i.e, 15 (75%) of patients with pruritus reported exacerbation during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of pruritus with dry skin was reported by 13 (65%) patients. Morton et al 8 revealed lower hydration of stratum corneum in uremic patients with pruritus and dry skin promotes sensation of itch by lowering the threshold for itch. In our study majority i.e, 15 (75%) of patients with pruritus reported exacerbation during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…72 Several additional non-controlled trials have also shown the beneficial effects of compounds containing emollient creams in patients with xerosis and CKD-aP. 71,[73][74][75][76] In a prospective clinical trial, 200 g of a aqueous cream applied twice daily significantly improved pruritus severity in 16 out of 21 recruited dialysis patients and resulted in the abatement of itching in 9 patients. 75 In a prospective study of 21 HD patients, all treated with structured physiological lipids and endogenous cannabinoids twice daily for 3 weeks, pruritus severity was significantly reduced at the end of the treatment period and pruritus completely abated in 8 of 21 participants.…”
Section: Xerosis Treatmentmentioning
confidence: 99%
“…71,[73][74][75][76] In a prospective clinical trial, 200 g of a aqueous cream applied twice daily significantly improved pruritus severity in 16 out of 21 recruited dialysis patients and resulted in the abatement of itching in 9 patients. 75 In a prospective study of 21 HD patients, all treated with structured physiological lipids and endogenous cannabinoids twice daily for 3 weeks, pruritus severity was significantly reduced at the end of the treatment period and pruritus completely abated in 8 of 21 participants. 76 However, despite the proven effectiveness of emollient creams in treating xerosis, no trials have tested its effect on pruritus in a double-blind, placebo-controlled fashion.…”
Section: Xerosis Treatmentmentioning
confidence: 99%
“…It was seen that xerosis was more common in diabetics and in our study diabetes was the most common reason of CKD. One study revealed lower levels of stratum corneum hydration as the cause of xerosis but another study implicated reduction in the size of eccrine glands as the cause 7,11 . Hyperpigmentation was seen in 30 (25%) patientswhich was similar to various other studies 11 .…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed lower levels of stratum corneum hydration as the cause of xerosis but another study implicated reduction in the size of eccrine glands as the cause 7,11 . Hyperpigmentation was seen in 30 (25%) patientswhich was similar to various other studies 11 . Failure of the kidneys to secrete beta-melano-stimulating hormone resulting in increased deposition of melanin in the skin has been implicated for this 12 .…”
Section: Discussionmentioning
confidence: 99%